2013
DOI: 10.1063/1.4798288
|View full text |Cite
|
Sign up to set email alerts
|

Threshold current for switching of a perpendicular magnetic layer induced by spin Hall effect

Abstract: We theoretically investigate the switching of a perpendicular magnetic layer by in-plane charge current due to the spin Hall effect. We find that, in the high damping regime, the threshold switching current is independent of the damping constant, and is almost linearly proportional to both effective perpendicular magnetic anisotropy field and external in-plane field applied along the current direction. We obtain an analytic expression of the threshold current, in excellent agreement with numerical results.Base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
242
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 311 publications
(268 citation statements)
references
References 42 publications
17
242
4
Order By: Relevance
“…5a,c using Ti(1)/Co 40 Fe 40 B 20 (0.85)/Pt(5). We then numerically simulated the curves based on equation (8) and equation (9), also shown in Fig. 5a,c.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5a,c using Ti(1)/Co 40 Fe 40 B 20 (0.85)/Pt(5). We then numerically simulated the curves based on equation (8) and equation (9), also shown in Fig. 5a,c.…”
Section: Discussionmentioning
confidence: 99%
“…One way to realize electrical control of magnetization is to leverage the spin-orbit interaction (SOI), through which an electric current exerts an effective field and torque on the magnetization 5,6 . In recent years, electric-current-induced magnetization switching in heavy metal (HM)/ferromagnetic metal (FM) bilayers has attracted great attention because of its high efficiency in magnetization switching, architectural simplicity and potential to couple with voltage-controlled magnetic anisotropy 7,8 . Besides magnetization switching, the SOI effect also provides a convenient tool to manipulate magnetic domains [9][10][11][12][13] .…”
mentioning
confidence: 99%
“…By contrast, in the SO-STT switching, only the interference between the read and breakdown voltages matters, since the writing is governed mainly by an in-plane current. Another important merit of the SO-STT switching is that it allows a faster switching than the standard STT switching since the SO-STT switching is completed through only half a precession in contrast to the standard STT switching [25].…”
mentioning
confidence: 99%
“…This current induced switching has been attributed to so called spin-orbit torques (SOTs) due to the spin-Hall effect (SHE) [2][3][4][5][6] and the Rashba effect 1,[7][8][9] , arising from spin-orbit coupling and broken inversion symmetry at the heavy-metal/ferromagnet interface. SOT switching has been studied theoretically 6 and experimentally for Pt/Co/AlO x 1,3,7,10 , Pt/Co/Pt 11 , Ta/CoFeB/MgO 12 , Pt/CoFe/MgO 5 and Ta/CoFe/MgO 5 nanodots and nanostrips 4,5,13,14 , and may provide an efficient means to operate ferromagnetic memories 15 such as SOT-MRAM or racetrack memories 16 . More recently, it has been shown that the Dzyaloshinskii-Moriya interaction (DMI) plays an important role in domain wall (DW) motion in such materials 5,[17][18][19][20] and may also be important in SOT switching 21 .…”
mentioning
confidence: 99%